PENERAPAN MODEL VAK (VISUAL AUDIO KINESTHETIC) PADA TEKS IKLAN PADA SISWA SMP - Ratih Radiawati; Siti Habibah Noor Saadah; Teti Sobari (IKIP Siliwangi, 2019)
The main problem of this research is the lack of understanding of students about writing ad text, so that a learning model that is able to overcome this problem is needed, one of which is the VAK model. This study aims to improve the learning outcomes of junior high school students regarding ad text material using the VAK (Kinesthetic Visual Audio) model. One group pretest-posting desing was used as a research method. Class VIII research subjects totaling 33 students, the results of the study concluded that students could understand ad text with the VAK (Visual Audio Kinesthetic) model. The conclusion is seen in the results of the student test, on the first test with an average of 66.96% experiencing an increase in the final test because it had received treatment to be 99.03%.